Propagation dynamics for a competitive-cooperative recursion system with monostable structure - Renhu Wang; Xuezhong Wang (Mathematics Open)
In this study, monostable traveling wave solutions were considered for a competitive-cooperative recursive system. We demonstrate the existence of monostable traveling wave solutions for these systems under suitable conditions by employing the theory of monostable wave in the context of monotone semiflows. Additionally, the global stability for these monostable traveling wave solutions was established through a dynamical systems approach.